Vascular surgery in rural areas: abdominal aortic aneurysm surgery with prosthesis in a tertiary hospital in Haiti: a case report - Fleury, Marline; Plaisimond, Peterson; Jacques, Flawendjee Djaweelentz; Menager, Roody; Regulus, Rocky; Jean Louis, Mac Lee (International Surgery Journal, 2026)
Open surgery was replaced in the 1990s by endovascular repair (EVAR), a less invasive method that benefits many patients. However, he remains inaccessible in resource-limited countries, where surgery faces many obstacles. This article explores a case of aorto-iliac aneurysm in a young adult treated in a rural area with limited resources, highlighting the challenges and possibilities of surgical interventions performed under restrictive conditions. A 43-year-old hypertensive man with a 5-year history of abdominal mass presented with abdominal pain and mass. Examination revealed a left-sided pulsatile abdominal mass with thrill. Ultrasound showed a 71.8 mm infrarenal aorto-iliac aneurysm with 39 mm common iliac artery diameter. He underwent successful open repair with a bifurcated prosthesis after stabilization and optimization. CT angiography is the gold standard for diagnosing abdominal aortic aneurysm, allowing accurate assessment and planning. In our context, planning was based on Doppler ultrasound due to limited access to CT angiography. Preparing for open repair of abdominal aortic aneurysms (AAA) also involves optimizing comorbidities, a functional blood bank, and invasive monitoring. In this case, limitations included a lack of CT scanning, minimal blood resources, no invasive intraoperative hemodynamic monitoring and reports indicated that a Doppler ultrasound confirmed the success of the graft. These shortcomings theoretically increase surgical risk, reflecting realities in resource-limited hospitals. This case shows open AAA surgery is feasible in constrained environments with good preparation and adaptation. Although EVAR is effective, open surgery remains crucial in certain situations.